How to calculate step response for $y''(t) - y(t) = x'(t) - x(t)$ in time domain? So, without Laplace or Fourier Transforms.

This is what I tried:

The Homogeneous solution of the differential equation would be: $ y_{homogeneous} = A*e^t + B*e^{-t} $.

u(t) is the unit step function. When I try to fill in the stepfunction for x: x(t)=u(t). So x'(t) = u'(t) = $\delta(t)$

And I try a step response $y= s= y_{homogeneous}*u(t) = (A*e^t + B*e^{-t})*u(t) $

$\frac{\partial ^2 ( \left(A e^t+B e^{-t} \right)u(t) )}{\partial t^2}-\left(A e^t+B e^{-t}\right) u(t)=\delta(t)-u(t)$

So, I will get:

$2 (A-B) \delta(t)-A \delta(t)+A \left( \delta ' (t) \right )+B \delta(t)+B \left( \delta ' (t) \right)=\delta(t)-u(t)$

But there's no u(t) at the left hand side.


1 Answer 1


Multiply with $e^{-t}$. Then the ODE can be rewritten as $$ (e^{-t}y')'+(e^{-t}y)'=(e^{-t}x)' $$ which integrates to $$ y'+y=x+Ce^t $$ This removes the need to introduce distributions. Now integrate to the left and to the right of the jump and adjust the two integration constants on both sides in such a way that the combined function is continuous.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.